Application of Dhikr Therapy to Auditory Hallucination Patients at Prof. Dr. M. Ildrem Mental Hospital, North Sumatra - Rafika Nur Siregar; Lily Putri Marito; Irma Widya Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
Hallucinations are a perceptual disorder in which patients perceive something that is not actually happening. The application of dhikr therapy in hallucinatory patients aims to control hallucinations, because this aspect is shown to maximize the benefits, treatment and feelings of peace for patients with hallucinations. Method: case study design using a descriptive method with a nursing process approach in 5 patients focused on one of the important problems in the case of auditory hallucination nursing care. Patients were taught dhikr therapy by reading tasbih ( Suhanallah ) 33 times, tahmid (alhamdulillah) 33 times and takbir ( Aallahu Akbar) 33 times, this therapy was carried out 2 times a day for 7 days with a duration of 15 minutes. The instrument used in the study was AHRS. Results: The first respondent to the implementation of dhikr therapy found an AHRS score of 25 to 13. In the second respondent to the implementation of dhikr therapy found an AHRS score of 26 to 14. In the third respondent to the implementation of dhikr therapy found an AHRS score of 24 to 13. the implementation of dhikr therapy found an AHRS score of 26 to 13. Conclusion: dhikr therapy is effective in reducing the frequency and intensity of auditory hallucinations and increasing the calmness of patients with auditory hallucinations.